Humanizing Learning in Higher Education: Pengalaman Mahasiswa dalam Pembelajaran Berbasis Humanistik pada Era Artificial Intelligence - Rezi Syaputri; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
Artificial Intelligence (AI)-based learning has become a focus of various studies, but research that specifically explores students’ experiences in humanistic learning in the AI era remains limited. This study aims to explore students’ experiences in humanistic-based learning and to understand how humanistic values are maintained amid the use of AI in higher education. This study used a qualitative approach with a phenomenological design, involving 12 undergraduate students selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using Colaizzi’s phenomenological analysis technique. The results show four main themes, namely AI as a learning facilitator, the importance of humanistic interaction in learning, dilemmas in the use of AI in academic activities, and students’ expectations regarding the integration of AI and humanistic learning. The findings show that AI provides easier access to information, increases learning efficiency, and supports understanding of course material. However, students still view interaction with lecturers, empathy, dialogue, and reflection as essential elements that cannot be replaced by technology. The use of AI also raises challenges in the form of potential dependence, a decline in critical thinking skills, and issues of academic ethics. The conclusion of this study emphasizes that AI needs to be positioned as a supporting instrument for learning, while the humanistic approach remains the foundation for creating meaningful learning experiences. This study contributes to the development of the concept of humanizing learning in the digital transformation of higher education and provides implications for universities in designing ethical, adaptive, and student-centered AI-based learning policies and strategies.